EFEKTIVITAS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENGOPTIMALISASI PELAYANAN GERAKAN INDONESIA SADAR ADMINISTRASI KEPENDUDUKAN (GISA) DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Candra, Aprian; Suprayogo, Tjahyo; Sinaga, Jona Bungaran Basuki (Ensiklopedia of Journal, 2024)
Abstract: population documents. One of the contributing factors is the lack of strategic location of mobile population services and the lack of optimal socialization of the Indonesian Population Awareness Administration Movement (GISA) by the Population and Civil Registration Service to the community in Kuantan Singingi Regency. The aim of this research is to determine and analyze the effectiveness, inhibiting and supporting factors, as well as strategies for overcoming inhibiting factors from the Population and Civil Registration Service in optimizing GISA in Kuantan Singingi Regency, Riau Province. Method: This research uses descriptive qualitative research. The research results showed that the Population and Civil Registration Service carried out various programs to optimize GISA services in Kuantan Singingi Regency. as stated in the Regional Medium Term Development Plan (RPJMD). Conclusion: The Population and Civil Registration Service of Kuantan Singingi Regency is innovating population services to make it easier for the people of Kuantan Singingi Regency to manage and update population documents.Keywords: GIS optimization, RPJMD synchronization, Kuantan Singingi.